Penerapan Teknik Butterfly Hug Untuk Menurunkan Kecemasan Pada Lansia Dengan Penyakit Diabetes Melitus - Rokhmat, Miftakhur; Rohpiani, Suci; Rahmawati, Arni Nur; Sundari, Ririn Isma (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
The elderly is the final phase of the individual's developmental process characterized by various physical, emotional, and mental changes that may lead to various health issues, one of which is anxiety. The aim of this community service activity is to enhance the knowledge and skills of the elderly regarding the Butterfly Hug technique as an effort to reduce anxiety levels. This community service method is carried out through lectures and demonstrations held in two meetings on April 12, 2025, and May 10, 2025. The first meeting included a pretest on anxiety levels, counseling, and a demonstration of the Butterfly Hug technique. The second meeting included a posttest and a re-demonstration of the Butterfly Hug technique questionnaire. This activity was conducted at the Sokaraja 1 Health Center and involved 68 elderly participants. The results of the pretest showed an average anxiety score of 48.14, with the highest score being 54 and the lowest score being 38, while the posttest results indicated a decrease in the average anxiety score to 40.32, with the highest score being 51 and the lowest score being 36. This activity aims to empower the elderly with the knowledge and skills about the Butterfly Hug Technique which is needed to reduce anxiety levels.